Effect of ultraviolet radiation on the skin - Glodianytė, Indrė; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2021)
The beneficial effect of ultraviolet radiation on our skin manifests itself in the synthesis of vitamin D. However, the detrimental effect of this radiation is much more severe. A longer duration of the effect of this radiation speeds up photoaging of skin depending on its phonotype. Symptoms of burning accompanied by tiredness, headaches, changes in temperature, skin damage observed testify to the negative effect of ultra-violet radiation. The unsuitable acquisition of measures of protection with SPF (Sun Protection Factor) numbers and their seasonal application presuppose the formation of wrinkles. This issue remains relevant today as well, because the results of ultraviolet radiation are diagnosed ever more often. They testify to careless skin care. The slightest skin redness, swelling or brownness is reaction of the skin to harmful ultraviolet radiation. The aim of the investigation was to examine the effect of ultraviolet radiation on skin. The investigation was carried out in virtual space on the Internet website www.apklausa.lt in 2021 (2 months). A total of 209 respondents took part in the investigation. The results and conclusions of the investigation are as follows: due to the nature of work, about half of the respondents were exposed to ultraviolet radiation the whole day or 3–4 hours a day. One the third of the respondents used the solarium procedures once per week, provided themselves with measures of protection in shops; however, they did not set great store by the protective effect of SPF filters. One the sixth of the respondents used measures of protection when their skin suffered serious damage.
Keywords: photoaging; skin damage; measures of protection